Simulasi pemasangan sebuah model kerugian minor perubahan penampang di konektor loop mesin termoakustik - Nurpatria, N.; Mirmanto, M.; Joniarta, I.W.; Padang, Y.A.; Susana, I.G.B. (Universitas Mataram, 2023)
A custom-designed thermoacoustic engine model has been created with the open source Delta EC simulation software. The specific design of the engine lies in the part of the heat exchanger, which allows it to receive heat from the hot gas stream resulting from the combustion of low grade biomass directly. The engine model can be coupled with a loudspeaker model that functions as a liner alternator, resulting in a simple power generator engine model. In this study, further simulations were carried out to increase the total efficiency of converting heat energy into electricity from the previous model. After that a model of minor loss of cross-sectional change was also added to the model. In a certain set of engine model parameter values without minor losses, the efficiency of converting heat energy to acoustic energy is 12.76%, equivalent to the amplification of acoustic energy by a regenerator of 33.26 W. The total efficiency of the engine model in converting heat energy into electrical energy is 10.53%. After the addition of a sub-program of minor losses due to the effect of one conical segment, there was an acoustic energy loss of 0.11 W. So that the efficiency of converting heat energy to acoustic energy was reduced by 0.01% to 12.75%. As a result, relatively small change occur in the total efficiency of the engine model.